Intravascular ultrasound-guided percutaneous coronary intervention for patients with coronary bifurcation lesions: A systematic review and meta-analysis. Issue 37 (11th September 2020) - Yang, Rong-Rong; Lv, Yong-Hui; Guo, Chen; Li, Min; Zhang, Ming-Bo; Wang, Zhi-Lu; Meng, Ying
Abstract: Background and Objective: Intravascular ultrasound (IVUS) could take on a vital position when angiographic images are not clear enough to be precisely visualized or measured by computer-aided technology. This meta-analysis was designed to compare the benefits of IVUS-guided and angiography-guided percutaneous coronary intervention(PCI) strategies for improving clinical outcomes. Methods: PubMed, Embase, Web of Science, and Cochrane Library were searched for articles published from inception to 13th October, 2019. A comparative study of IVUS-guided and angiography-guided PCI strategies for patients with coronary bifurcation lesions was retrieved. The early endpoint events (⩽1 year) and the late endpoint events (>1 years) were determined according to the follow-up time. The former included cardiac death, target lesion or vessel revascularization, stent thrombus, and major adverse cardiac events, while the latter included cardiac death. Statistical software Review Manager Version 5.3 was performed for meta-analysis. Results: Five studies involving7, 830 patients with coronary bifurcation lesions were included in this meta-analysis, the incidence of major adverse cardiac events for IVUS-guided strategy in patients with coronary bifurcation lesions were lower than those of patients with angiography-guided strategy at the early follow-up(OR = 0.55, 95% CI 0.42 - 0.70, P   <  .0001).Meanwhile, cardiac death, target vessel or target lesion revascularization, stent thrombosis were not statistically significant(OR = 0.68, 95% CI 0.34 - 1.35, P  = .27; OR = 0.78, 95% CI 0.59 - 1.05, P  = .10; OR = 0.36, 95% CI 0.12–1.04, P  = .06).However, significant differences in cardiac death between IVUS-guided and angiographic-guided strategies were observed in the late follow - up (OR = 0.36, 95% CI 0.23 - 0.57, P  < .00001). Conclusion: The IVUS-guided PCI strategy was associated with more clinical benefits compared with angiography-guided PCI strategy in patients with coronary bifurcation lesions. These findings suggest that the IVUS-guided PCI strategy can be recommended as an optimization in this kind of patients.